Effect of Biochar and Compost from Chicken, Goat, and Cow Manure on Cultivation of Red Chili (Capsicum annuum L) - Kadek Adi Mahendra; Yohanes Parlindungan Situmeang; Made Suarta (Warmadewa University Press, 2020)
Abstract This study aims to determine the effect of compost and biochar fertilizer at a dose of 15 tons ha-1 made from livestock manure and its interaction on the growth and yield of red chili plants. This research was conducted in Blahkiuh Village, Abiansemal District, Badung Regency, Bali with an altitude of 400-500 m above sea level. This research was started from February 2020 to July 2020. The design used in this study was a factorial randomized block design (RBD) consisting of 2 factors, namely: chicken compost with 4 levels and biochar 2 levels by testing the types of compost and biochar. The interaction between the treatment effect with the type of compost and the type of chicken biochar had no significant effect on all observed variables. The treatment of compost application had a significant to very significant effect on most of the observed variables, except for the number of leaves, which had no significant effect. The treatment of chicken biochar dosing had a significant to very significant effect on most variables except for the maximum number of leaves and fresh weight per fruit, which had no significant effect. The results showed that the highest fresh fruit weight was obtained in the type of compost given by chicken livestock, namely 1499.56 g or an increase of 46.46% compared to the lowest treatment obtained without compost, namely 1023.85 g. To increase the growth and yield of red chili plants, it is recommended to use compost types of chicken livestock and chicken biochar at a dose of 15 tonnes ha-1 and further research is needed on the provision of biochar and compost types at different locations and types of plants. Keywords: compost, biochar, and chili plants.